Homozygous Antithrombin Deficiency Type II (99 Leu to Phe Mutation) and Childhood Thromboembolism - Kuhle, Stefan; Lane, David A.; Jochmanns, Kristin; Male, Christoph; Quehenberger, Peter; Lechner, Klaus; Pabinger, Ingrid (Thrombosis and Haemostasis, 2001)
We report 5 children from 3 families with homozygous antithrombin deficiency type II affecting the heparin binding site (99 Leu to Phe mutation). Four children had severe spontaneous thromboembolic events (deep leg or caval vein thrombosis, ischaemic stroke) at one week, 3 months, 13 and 14 years of age. The fifth patient, a 17 year-old boy was asymptomatic. Early manifestation of homozygous deficiency calls for prompt and accurate diagnosis. In doubtful cases genetic analysis is required. Long-term oral anticoagulation should be considered in affected individuals.
Keywords: Antithrombin-deficiency; thromboembolism; children